Mesonephric Adenocarcinoma of Uterine Cervix; A Case Report and Review of the Literature - Fatemeh Nili; Samaneh Salarvand; Hana Saffar; Bita Kalaghchi; Reza Ghalehtaki (Iranian Society of Pathology, 2020)
Mesonephric adenocarcinoma of the uterine cervix, an extremely rare tumor of the female genital tract, derives from the remnants of embryonic mesonephric ducts and its prognosis, diagnosis and treatment is rather challenging. We report a case of a 46-year-old woman with history of abnormal uterine bleeding and an enlarged uterine cervix on physical examination without obvious mass lesion. She was clinically underdiagnosed with cervical myoma and mesonephric hyperplasia. After simple hysterectomy, stage IB2 mesonephric adenocarcinoma was diagnosed. Despite adjuvant chemoradiation, she presented with peritoneal and locoregional recurrence in less than a year. In the presence of abnormal bleeding and cervical mass, mesonephric hyperplasia in cervical biopsy specimen should be suspected for adenocarcinoma. Radical hysterectomy and complete staging with or without salpingo-oophorectomy is the mainstay of treatment. Despite all ambiguities, due to small number of the reported cases, the overall prognosis seems to be less favorable than conventional cervical adenocarcinoma.